Physical and Sensory Properties of Instant Tiwul from Cassava Flour and Mocaf with Addition of Yellow Pumpkin Flour - Ikhsani, Atika Yahdiyani; Wijatniko, Bambang Dwi; Afifah, Ika Qurroatul (Program Studi Teknologi Pangan, 2023)
Instant tiwul is commonly made from cassava flour which product specification was characterized by its properties. However, some sensory attributes of instant tiwul were not desirable. In addition, the nutritional quality of instant tiwul needs to be improved by the addition of micronutrients. The substitution of cassava flour with mocaf flour and supplemented with yellow pumpkin flour is expected to improve the physical and sensory quality of the product, as adding nutritional value of instant tiwul that enriched with vitamin A. This study was conducted in a group-randomized trial with the substitution of yellow pumpkin flour with variation of 0, 10, 20% to cassava flour and mocaf flour. Physical properties (water content, water absorption, color) and sensory properties (acceptance test) were evaluated. The result indicated that the addition of yellow pumpkin flour lowered the water content on instan tiwul from both cassava flour and mocaf flour. The addition of yellow pumpkin flour significantly increased the water absorption of instant tiwul from cassava flour, however it reduced on mocaf flour formula. Water absorption of instant tiwul from mocaf with 0% yellow pumpkin flour is the highest with 45,27%. There is significant change on L, a and b parameter of instant tiwul color with addition of yellow pumpkin flour. Sensory evaluation suggested that there is significant change on acceptance of aroma, taste, texture, and overall likeness from instant tiwul made from mocaf flour with addition of yellow pumpkin flour, however cassava flour with addition of yellow pumpkin flour showed least significant change on sensory properties.Â